The Integration of Multimodality Care for the Treatment of Small Cell Lung Cancer in a Rural Population and Its Impact on Survival. (October 2015) - Lee, Kiwhoon; Kloecker, Goetz; Pan, Jianmin; Rai, Shesh; Dunlap, Neal E.
Abstract : Objectives: Many factors and disparities contribute to the multidisciplinary management of small cell lung cancer (SCLC). Our objective was to conduct a cancer registry analysis of patients with SCLC in Kentucky to identify factors affecting treatment choice and mortality. Methods: Database collection was done through the Kentucky Cancer Registry, which is part of the Surveillance, Epidemiology, and End Results program. Patients diagnosed between 1995 and 2008, diagnosed with SCLC, and AJCC stage I through IV were included. Statistical analyses were performed to identify variables affecting initial treatment choice and survival. Results: Analysis evaluated 4814 patients from the Kentucky Cancer Registry. For extensive stage, age ( P <0.001) and urban versus rural county ( P =0.03) were significantly associated with the type of treatment received. Age was the only variable impacting treatment choice in limited-stage patients. Limited stage patients were more likely to receive chemotherapy and radiation (chemoRT; 54.6% vs. 46.5%). On multivariate analysis, for extensive stage patients, age at diagnosis, male sex, and treatments other than chemoRT were variables associated for increased risk of death. In limited stage patients, increasing age, and treatments other than chemoRT were variables associated with increased risk of death. Survival was significantly improved in both limited stage and extensive stage patients that received chemoRT compared with chemotherapy only, radiation only, or no treatment. Conclusions: Treatment with chemoRT was associated with improved survival in patients with limited and extensive stage SCLC. In these patients, socioeconomic, racial, or geographic factors did not impact the type of treatment received or survival.